Separation and recovery of arsenic and alkali products during the treatment of antimony smelting residues. (1st July 2020) - Long, Hua; Zheng, Ya-jie; Peng, Ying-lin; Jin, Gui-zhong; Deng, Wei-hua; Zhang, Shou-chun; He, Han-bing
Highlights: Efficient separation and recovery of arsenic and alkali were achieved. Low consumption of sulfuric acid in the process of deep alkali removal. The products recovered from arsenic-alkali solution were Na2 CO3 and As2 O3 . No arsenic-alkali mixed salts were produced in the separation process of arsenic and alkali. Abstract: For the comprehensive utilization of antimony smelting arsenic-alkali residue, there are some problems such as the incomplete separation and low recoveries of arsenic and alkali, and the formation of arsenic-alkali mixed salts with secondary pollution. In order to solve these problems, the leaching solution of arsenic-alkali residue (arsenic-alkali solution) was used as a raw material in this study, and a novel process of twice alkali recovery with CO2, deep alkali removal with H2 SO4, As(V) reduction with SO2 and evaporation concentration to recover arsenic was proposed to dispose of the arsenic-alkali solution. The total recovery of alkali was 87.8% by twice alkali recovery from the arsenic-alkali solution. After washing and thermal decomposition of crude NaHCO3, the obtained Na2 CO3 product can be used as the reagent of arsenic removal in the refining process of crude antimony. In the process of deep alkali removal, compared with the direct treatment, the consumption of H2 SO4 after twice alkali recovery was markedly reduced from the arsenic-alkali solution, and also no mirabilite was precipitated. The total recovery of arsenic was 80.6% in the process of arsenic recovery, and the purity of As2 O3 in arsenic trioxide product reached 95.2% after washing, which meets the third grade standard of arsenic trioxide (GB 26721–2011). This process realizes the efficient separation and recovery of arsenic and alkali from the arsenic-alkali solution, and also no arsenic-alkali mixed salts are produced.